Compromised Motor Dexterity Confounds Processing Speed Task Outcomes in Stroke Patients - Low, Essie; Crewther, Sheila Gillard; Ong, Ben; Perre, Diana; Wijeratne, Tissa (Frontiers in Neurology, 2017)
Most conventional measures of information processing speed require motor responses to facilitate performance. However, although not often addressed clinically, motor impairment, whether due to age or acquired brain injury, would be expected to confound the outcome measure of such tasks. The current study recruited 29 patients (20 stroke and nine transient ischemic attack) with documented reduction in dexterity of the dominant hand, and 29 controls, to investigate the extent to which three commonly used processing speed measures with varying motor demands (a Visuo-Motor Reaction Time task, and the WAIS-IV Symbol Search and Coding subtests) may be measuring motor-related speed more so than cognitive speed. Analyses include correlations between indices of cognitive and motor speed obtained from two other tasks (Inspection Time and Pegboard Task respectively) with the three speed measures, followed by hierarchical regressions to determine the relative contribution of cognitive and motor speed indices towards task performance. Results revealed that speed outcomes on tasks with relatively high motor demands, such as Coding, were largely reflecting motor speed in individuals with reduced dominant hand dexterity. Thus, findings indicate the importance of employing measures with minimal motor requirements, especially when the assessment of speed is aimed at understanding cognitive rather than physical function.